International reserve pooling in the West African monetary union (2012)
The paper has focused on international reserve pooling in the West African region. Attempts have been made to situate the demand for and adequacy of foreign reserve in ECOWAS member countries. This is done in order to appreciate the adequacy of pooled reserve and its management in the ECOWAS envisaged monetary union. The gains and losses that are concomitant to having a monetary union at regional level for ECOWAS member states are equally investigated. The paper has established that the evolution of a monetary union for ECOWAS has been hindered largely by the inability of the member states to actualize both the primary and secondary convergence criteria even when the set timeline has since elapsed. ECOWAS sub-region cannot afford to be left out of the race toward regional integration. At the centre of the integration process is monetary integration as this will lubricate all other dimensions of regional integration such as trade integration. Regional collaboration has no substitute in the global economy and as such, the journey towards ECOWAS monetary integration involving pooling of reserve and evolution of single currency is a worthy venture.